Thick escaping magnetospheric ion layer in magnetopause reconnection with MMS observations. Issue 12 (28th June 2016) - Nagai, T.; Kitamura, N.; Hasegawa, H.; Shinohara, I.; Yokota, S.; Saito, Y.; Nakamura, R.; Giles, B. L.; Pollock, C.; Moore, T. E.; Dorelli, J. C.; Gershman, D. J.; et al.
Abstract: The structure of asymmetric magnetopause reconnection is explored with multiple point and high‐time‐resolution ion velocity distribution observations from the Magnetospheric Multiscale mission. On 9 September 2015, reconnection took place at the magnetopause, which separated the magnetosheath and the magnetosphere with a density ratio of 25:2. The magnetic field intensity was rather constant, even higher in the asymptotic magnetosheath. The reconnected field line region had a width of approximately 540 km. In this region, streaming and gyrating ions are discriminated. The large extension of the reconnected field line region toward the magnetosheath can be identified where a thick layer of escaping magnetospheric ions was formed. The scale of the magnetosheath side of the reconnected field line region relative to the scale of its magnetospheric side was 4.5:1. Key Points: The structure of magnetopause reconnection is determined with ion distribution observations Streaming and gyrating ions are discriminated in the reconnected field line region The large extension of the reconnected field line region toward the magnetosheath